E-SERVICES IN THE FIELD OF REAL ESTATE - Čakāne, Ilze; Seržants, Austris; Grabusts, Pēteris (HUMAN. ENVIRONMENT. TECHNOLOGY. Proceedings of the Students International Scientific and Practical Conference, 2016)
The aim of the paper is to research the popularity and advantages of e-services, as well as the types of real estate related e-services offered by local governments within the Unified system and the real estate related functions available for people on the e-service portal. The study showed that local governments do not use the potentialities offered by the Unified system to the full extent and only 23 of all the local governments have joined the NOMA e-services that allow its users to view all information about local government leaseholds, apply for a lease as well as make payments and perform other actions. Rezekne region local government must join this service in order to ensure convenient and contemporary solution to local government’s real estate matters.